2009
DOI: 10.1590/s1677-04202009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals, Co, Ni, Cu, Zn and Cd, produce oxidative damage and evoke differential antioxidant responses in spinach

Abstract: Exposure of 10-d-old spinach (Spinacea oleracea L.) plants to excess (500 µM) concentrations of Co, Ni, Cu, Zn and Cd in sand culture inhibited growth, induced toxicity symptoms, oxidative damage and changes in the antioxidant defense system. The severity of the metal-induced effects varied with the metals and the duration of exposure to excess supply of the metals. Each metal induced chlorosis. In addition, excess Co, Ni and Cd also produced metal specific toxic effects. Excess supply of each metal caused lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 26 publications
7
36
0
1
Order By: Relevance
“…Particularly, the correlation coefficient was highest for Cd among the heavy metals with the SSB-H treatment for the spinach (0.719). A similar trend was observed when heavy metals' effectiveness in producing oxidative damage on spinach, assessed by the manifestation of external visual toxicity effects, was in the order of Zn<Cu<Cd (Pandey et al, 2009). Interestingly, however, the bean shoot showed Cd tolerance to some degree with the SSB-L treatment in this study (its correlation coefficient was positive).…”
Section: Plant Absorption Of Heavy Metalsupporting
confidence: 71%
See 1 more Smart Citation
“…Particularly, the correlation coefficient was highest for Cd among the heavy metals with the SSB-H treatment for the spinach (0.719). A similar trend was observed when heavy metals' effectiveness in producing oxidative damage on spinach, assessed by the manifestation of external visual toxicity effects, was in the order of Zn<Cu<Cd (Pandey et al, 2009). Interestingly, however, the bean shoot showed Cd tolerance to some degree with the SSB-L treatment in this study (its correlation coefficient was positive).…”
Section: Plant Absorption Of Heavy Metalsupporting
confidence: 71%
“…Accumulation of heavy metals (Cu, Zn, and Cd) in spinach after exposure to 500 µM supply of the metals was greater in the root than in the leaf and stem at the end of experiment (Pandey et al, 2009). The rate of heavy metal absorption by the plant can be affected by many factors of both soil and plant such as soil pH, plant age, plant species, and nature of soil and climate (Alloway & Ayres, 1997; Uwah, 2009).…”
Section: Plant Absorption Of Heavy Metalmentioning
confidence: 87%
“…The present study showed that CAT enzyme activity in V. olympicum seedlings is sensitive to high Cu concentrations and its activity is inhibited in treatments with such high Cu concentrations. In fact, it has been reported that elevated Cu levels have an inhibitory effect on CAT activity [43]. Similar responses in CAT activity have also been described in several studies [44][45][46].…”
Section: Discussionsupporting
confidence: 79%
“…According to findings by Pandey et al (2009), abiotic stresses in plants exposed to excessive levels of heavy metals produce oxidative stress and stimulate antioxidative responses in different efficiencies. Also, according to Pandey et al (2009), the damage by oxidative action can be evaluated by external visual expression of toxicity of the elements in the order Ni> Co> Cd> Cu> Zn.…”
Section: Introductionmentioning
confidence: 99%
“…Also, according to Pandey et al (2009), the damage by oxidative action can be evaluated by external visual expression of toxicity of the elements in the order Ni> Co> Cd> Cu> Zn.…”
Section: Introductionmentioning
confidence: 99%